Tetramethyl bisphenol F cyanate ester and preparation method thereof
By introducing additional methyl groups and using montmorillonite-based bifunctional catalysts in the preparation process of bisphenol F cyanate, the problem of poor preparation purity and performance of bisphenol F cyanate is solved, and higher processability and heat resistance are achieved.
Patent Information
- Application Number
- CN202411694718.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-07
AI Technical Summary
The preparation purity of bisphenol F cyanate is not high and its performance is poor, especially when used in high-frequency electronic equipment and communication equipment, there are problems such as poor processing performance and insufficient moisture and heat resistance.
A method of preparing tetramethylbisphenol F cyanate is adopted to form tetramethylbisphenol F through a hydroxyaldehyde reaction, and tetramethylbisphenol F cyanate is formed through a nucleophilic substitution reaction. This method uses a montmorillonite-based bifunctional catalyst as a catalyst, simplifying the process steps and improving the reaction progress and product purity.
The processability and heat resistance of bisphenol F cyanate are improved, the viscosity of the resin is reduced, the flowability and performance of the material is improved, and the glass transition temperature and heat resistance are increased.
Smart Images

Figure BDA0005151833840000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cyanate esters, and particularly relates to tetramethyl bisphenol F cyanate and a preparation method thereof. Background Art
[0002] Cyanate resin refers to a phenolic derivative containing two or more cyanate functional groups, which can undergo a curing reaction under certain conditions to form a highly cross-linked three-dimensional network structure polymer. As a new type of resin with excellent performance, cyanate resin has many outstanding advantages compared with the currently widely used epoxy resins, bismaleimide resins and phenolic resins, such as stable and extremely low dielectric constant and dielectric loss, good heat resistance, thermal stability and wet heat stability, good flame retardancy, low smoke and ablation resistance, etc. It has broad application prospects in many fields such as aerospace, automobiles, electronics, and military industry, especially in high-speed digital and high-frequency printed circuit boards, high-performance wave-transmitting and stealth materials, and aerospace load-bearing structural materials.
[0003] Cyanate resins are divided into bisphenol A cyanate, bisphenol F cyanate and phenolic cyanate, among which bisphenol A cyanate has low cost and high mechanical properties and is a widely used cyanate resin. Compared with bisphenol A cyanate, bisphenol F cyanate has better processing performance, moisture and heat resistance, lower shrinkage and dielectric constant, and is more suitable for high-frequency electronic equipment and communication equipment. However, in order to obtain bisphenol F cyanate with better performance and higher purity, its processing and preparation technology has not been well optimized and disclosed. Summary of the invention
[0004] The object of the present invention is to provide a tetramethyl bisphenol F cyanate and a preparation method thereof, so as to solve the problem that the purity and performance of the bisphenol F cyanate are not high.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing tetramethyl bisphenol F cyanate, comprising the following process steps:
[0007] S1. Add 2,6-dimethylphenol to solvent A, raise the temperature to 45-55° C., and stir to dissolve to obtain a 2,6-dimethylphenol solution;
[0008] S2. adding formaldehyde to solvent A to obtain a formaldehyde solution having a mass fraction of 30 to 40%;
[0009] S3. Adding formaldehyde solution and montmorillonite-based bifunctional catalyst to 2,6-dimethylphenol solution, adjusting the reaction temperature to 50-70° C., stirring the reaction for 2-3 h, and then washing, vacuum distillation and drying to obtain a mixture of tetramethyl bisphenol F;
[0010] S4. The obtained mixture of tetramethyl bisphenol F is added to solvent B, triethylamine is added, and the mixture is stirred to obtain a pre-reaction solution;
[0011] S5. Add cyanogen chloride to solvent B, mix well and then add to the pre-reaction solution, adjust the reaction temperature to -5 to 0°C, stir the reaction for 1.5 to 2.5 hours, and then wash, dry, filter, vacuum distill and recrystallize to obtain tetramethyl bisphenol F cyanate;
[0012] The montmorillonite-based bifunctional catalyst is intercalated with composite quaternized chitosan.
[0013] Preferably, the addition amount of the montmorillonite-based bifunctional catalyst is 0.2-1.5% of the mass of 2,6-dimethylphenol.
[0014] Preferably, solvent A includes one of ethanol, methanol, acetone, dimethylformamide and ethyl acetate; solvent B includes one of butanone, toluene, dichloromethane and isopropanol.
[0015] Preferably, the molar ratio of 2,6-dimethylphenol to formaldehyde is 1:(0.55-0.6); the molar ratio of tetramethylbisphenol F, cyanogen chloride and triethylamine is 1:(2.3-2.6):(2-2.3).
[0016] By adopting the above technical scheme, the tetramethyl bisphenol F cyanate prepared by the present invention can reduce the interaction force between molecules by introducing additional methyl groups, reduce the viscosity of bisphenol F cyanate resin, improve the fluidity and processability of the material, and the methyl group can increase the rigidity of the molecule, improve the glass transition temperature of the resin, and increase the heat resistance. The tetramethyl bisphenol F cyanate of the present invention is mainly prepared by the nucleophilic substitution reaction of tetramethyl bisphenol F and cyanogen chloride, and triethylamine is also added. The triethylamine, as an alkaline ammonium salt, can play a certain alkaline catalytic role in the preparation process, and the triethylamine can react with the hydrogen chloride formed by the reaction to form an ammonium salt, which can not only reduce the emission of toxic gas hydrogen chloride, which is beneficial to separation from the product, but also promote the reaction to proceed in the forward direction by reducing the content of hydrogen chloride in the system.
[0017] Meanwhile, during the preparation process, 2,6-dimethylphenol and formaldehyde are reacted to obtain tetramethyl bisphenol F through an aldol reaction. Since the purity of tetramethyl bisphenol F will directly affect the purity, yield and performance of the product tetramethyl bisphenol F cyanate, it is necessary to avoid excessive impurities and side reaction compounds during the preparation of tetramethyl bisphenol F. The present invention adds a montmorillonite-based bifunctional catalyst during the preparation period, which can improve the reaction of tetramethyl bisphenol F to proceed in the forward direction and improve the purity of tetramethyl bisphenol F. The mixture of tetramethyl bisphenol F obtained by the reaction also contains montmorillonite-based bifunctional catalyst that has not been filtered. In the further reaction process, the montmorillonite-based bifunctional catalyst has acid-base active centers due to the intercalation of composite quaternized chitosan, and due to the special position of the acid-base centers, the acid-base centers will not quench each other, and the catalyst can continue to play a role, catalyzing the reaction between tetramethyl bisphenol F and cyanogen chloride, thereby further promoting the forward direction of the reaction and improving the purity of the product.
[0018] Preferably, the raw materials of the montmorillonite-based bifunctional catalyst include acid-activated sodium-based montmorillonite and quaternized chitosan in a mass ratio of 1:(0.75-0.85).
[0019] Preferably, the montmorillonite-based bifunctional catalyst is prepared according to the following method:
[0020] Preparation of acid-activated sodium montmorillonite: adding sodium montmorillonite to a strong acid aqueous solution with a mass fraction of 10 to 15%, stirring and mixing for 6 to 8 hours, centrifuging, washing and drying to obtain acid-activated sodium montmorillonite;
[0021] Preparation of quaternized chitosan: chitosan is added to water, the pH value of the solution is adjusted to 14-14.5, after stirring and mixing for 12-24 hours, a quaternary ammonium agent aqueous solution is added, and the reaction is stirred for 10-12 hours, and the quaternized chitosan is obtained by dialysis and freeze drying;
[0022] Preparation of montmorillonite-based bifunctional catalyst: acid-activated sodium montmorillonite is dispersed in water to obtain a montmorillonite suspension; quaternized chitosan is added to water, the pH value is adjusted to 4.5-5, stirred until completely dissolved and then added to the montmorillonite suspension, the temperature is increased to 50-60°C, stirred for reaction for 6-8h, and finally centrifuged, washed, neutralized, dried and ground to obtain a montmorillonite-based bifunctional catalyst.
[0023] Preferably, the quaternizing agent includes a combination of one or more of 2-chloroethylamine hydrochloride, 3-chloropropylamine hydrochloride, 2-bromoethylamine hydrochloride, 4-chlorobutylamine hydrochloride, 2-chloroethyltrimethylammonium chloride and (2-bromoethyl)trimethylammonium bromide.
[0024] Preferably, the mass ratio of chitosan to quaternary ammonium agent is 1:(5-6).
[0025] Preferably, the strong acid aqueous solution includes one of a sulfuric acid aqueous solution, a nitric acid aqueous solution and a hydrochloric acid aqueous solution.
[0026] By adopting the above technical solution, the montmorillonite-based bifunctional catalyst can utilize the large specific surface area and good heat resistance of montmorillonite to improve the catalytic activity of the catalyst, and is not easily restricted by reaction conditions. Specifically, in the preparation process of the montmorillonite-based bifunctional catalyst, the montmorillonite is first pretreated, and the acid-activated sodium-based montmorillonite can provide more acid sites. In a strong acid aqueous solution, hydrogen ions can exchange with cations between montmorillonite layers, and form free acids on the surface, activating and increasing the number and strength of Bronsted acid sites, thereby promoting the catalytic reaction of tetramethyl bisphenol F.
[0027] Moreover, more active end groups will be formed on the surface of montmorillonite after acid activation, which is conducive to the subsequent intercalation of quaternized chitosan. Chitosan is a natural high molecular alkaline polysaccharide with a large number of hydroxyl and amino groups distributed on the macromolecular chain. Quaternized chitosan can help weaken the hydrogen bonds between chitosan molecules, reduce the difficulty of intercalation with montmorillonite, and the quaternary ammonium groups contained in quaternized chitosan can provide alkaline sites for montmorillonite. Compared with general low molecular bases, macromolecular compounds as alkaline site carriers have higher structural stability and easy separation. After intercalation treatment, the interlayer spacing of montmorillonite increases, the interaction area also greatly increases, and the driving force of the intercalation reaction is increased, which can significantly improve the catalytic activity of the catalyst and maintain the structural properties of the montmorillonite itself.
[0028] The montmorillonite after the quaternary ammonium chitosan intercalation composite can have both acidic and basic sites, which can help catalyze the aldol reaction process of tetramethyl bisphenol F, and can also help catalyze the nucleophilic substitution reaction process of tetramethyl bisphenol F cyanate. The same catalyst can play a good catalytic performance and reduce the introduction of impurities in the reaction process. It not only simplifies the reaction process steps, but also improves the overall reaction progress and product purity, which is conducive to the formation of cyanate resins with better performance.
[0029] Preferably, the acid-activated sodium-montmorillonite is treated with magnesium ion exchange; the magnesium ion exchange treatment comprises the following steps: adding magnesium salt to a solvent, stirring and mixing, adding acid-activated sodium-montmorillonite, stirring and mixing at 50-60° C. for 5-6 hours, and finally filtering, washing and drying to obtain the acid-activated sodium-montmorillonite exchanged with magnesium ions.
[0030] Preferably, the magnesium salt comprises a combination of one or more of magnesium chloride, magnesium sulfate, magnesium nitrate and magnesium acetate; the added amount of the magnesium salt is 0.4-0.6% of the mass of the acid-activated sodium-based montmorillonite.
[0031] Preferably, the solvent includes a combination of one or more of ethanol, methanol, isopropanol, n-butanol, ethylene glycol and n-propanol.
[0032] By adopting the above technical scheme, the present invention further performs magnesium ion exchange treatment after acid-activating sodium-based montmorillonite. On the one hand, the number and activity of the acid-base sites of the montmorillonite-based catalyst can be increased, and the interlayer spacing of the montmorillonite can also be increased, which is conducive to the intercalation and recombination of quaternized chitosan. In addition, the treated montmorillonite interlayers have both sodium ions and magnesium ions, which can improve the selectivity of the catalytic reaction, attract the reaction raw materials to pass through the montmorillonite interlayers, improve the catalytic activity, and reduce the generation of side reaction products.
[0033] On the other hand, during the intercalation of quaternized chitosan with montmorillonite treated with magnesium ion exchange, the increase in active sites can help form a composite material with a porous structure, improve the binding force between quaternized chitosan and montmorillonite, prevent the loss of chitosan during the reaction, and avoid the introduction of new impurities and the decrease of catalytic activity.
[0034] In a second aspect, the present invention provides tetramethyl bisphenol F cyanate, which is prepared by the above-mentioned preparation method.
[0035] Beneficial effects of the present invention:
[0036] 1. The present invention provides a method for preparing tetramethyl bisphenol F cyanate, which can improve the processability and heat resistance of bisphenol F cyanate by introducing additional methyl groups. In the preparation process, tetramethyl bisphenol F is first formed by an aldehyde reaction, and then tetramethyl bisphenol F cyanate is generated by a nucleophilic substitution reaction. In the production process, only one catalyst, i.e., a montmorillonite-based bifunctional catalyst, is introduced to catalyze two reactions, thereby simplifying the process steps and improving the overall reaction progress and product purity.
[0037] 2. The montmorillonite-based bifunctional catalyst of the present invention is intercalated with a composite quaternized chitosan. The acid-activated montmorillonite provides a large number of acidic sites for the catalyst, and the quaternized chitosan provides a large number of basic sites for the catalyst. Due to the special position of the acid-base center, the acid-base center will not quench each other. After being treated with magnesium ion exchange, the structural stability and the bonding force between the composite materials can be further improved, the selectivity of the reaction catalyst is improved, and then the catalytic activity is improved. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Preparation Example
[0040] Preparation Example 1: A montmorillonite-based bifunctional catalyst was prepared according to the following method:
[0041] 10 g of sodium montmorillonite (ion exchange capacity 0.9 mmol / g) was added to a 10% nitric acid aqueous solution, stirred and mixed for 8 hours, and then centrifuged, washed and dried to obtain acid-activated sodium montmorillonite;
[0042] 10 g chitosan (weight average molecular weight 3.28 × 10 5 , deacetylation degree 85.6%) was added to 500 mL of water, the pH value of the solution was adjusted to 14, and after stirring and mixing for 24 hours, 55 g of 2-chloroethylamine hydrochloride was added, and the reaction was stirred for 12 hours. After dialysis and freeze-drying, quaternary ammonium chitosan was obtained;
[0043] Take 10g of acid-activated sodium-based montmorillonite and disperse it in 250mL of water to obtain a montmorillonite suspension; add 8g of the quaternized chitosan obtained above to 250mL of water, adjust the pH value to 4.5, stir until completely dissolved and then add it to the montmorillonite suspension, increase the temperature to 60°C, stir and react for 7h, and finally obtain a montmorillonite-based bifunctional catalyst through centrifugation, washing, neutralization, drying and grinding.
[0044] Preparation Example 2, a montmorillonite-based bifunctional catalyst, differs from Preparation Example 1 only in that the amount of quaternized chitosan added is 7.5 g.
[0045] Preparation Example 3, a montmorillonite-based bifunctional catalyst, is different from Preparation Example 1 only in that the amount of quaternized chitosan added is 8.5 g.
[0046] Preparation Example 4, a montmorillonite-based bifunctional catalyst, is different from Preparation Example 1 only in that the amount of quaternized chitosan added is 6 g.
[0047] Preparation Example 5, a montmorillonite-based bifunctional catalyst, is different from Preparation Example 1 only in that the amount of quaternized chitosan added is 10 g.
[0048] Preparation Example 6, a montmorillonite-based bifunctional catalyst, was prepared according to the following method:
[0049] 10 g chitosan (weight average molecular weight 3.28 × 105 , deacetylation degree 85.6%) was added to 500 mL of water, the pH value of the solution was adjusted to 14, and after stirring and mixing for 24 hours, 55 g of 2-chloroethylamine hydrochloride was added, and the reaction was stirred for 12 hours. After dialysis and freeze-drying, quaternary ammonium chitosan was obtained;
[0050] Take 10g of sodium montmorillonite (ion exchange capacity 0.9mmol / g) and disperse it in 250mL of water to obtain a montmorillonite suspension; add 8g of the quaternized chitosan obtained above to 250mL of water, adjust the pH value to 4.5, stir until completely dissolved and then add it to the montmorillonite suspension, increase the temperature to 60°C, stir and react for 7h, and finally obtain a montmorillonite-based bifunctional catalyst through centrifugation, washing, neutralization, drying and grinding.
[0051] Preparation Example 7, a montmorillonite-based bifunctional catalyst, was prepared according to the following method:
[0052] 10 g of sodium montmorillonite (ion exchange capacity 0.9 mmol / g) was added to a 10% nitric acid aqueous solution, stirred and mixed for 8 hours, and then centrifuged, washed and dried to obtain acid-activated sodium montmorillonite;
[0053] 10 g of acid-activated sodium montmorillonite was dispersed in 250 mL of water to obtain a montmorillonite suspension; 8 g of chitosan (weight average molecular weight 3.28 × 10 5 , deacetylation degree 85.6%) was added to 250 mL of water, the pH value was adjusted to 4.5, and the mixture was added to the montmorillonite suspension after stirring until completely dissolved. The temperature was raised to 60°C, and the reaction was stirred for 7 hours. Finally, the montmorillonite-based bifunctional catalyst was obtained by centrifugation, washing, neutralization, drying and grinding.
[0054] Preparation Example 8, a montmorillonite-based bifunctional catalyst, prepared according to the following method:
[0055] Take 10g of sodium montmorillonite (ion exchange capacity 0.9mmol / g) and add it to a 10% nitric acid aqueous solution. After stirring and mixing for 8 hours, centrifuge, wash and dry to obtain acid-activated sodium montmorillonite, which is a montmorillonite-based catalyst.
[0056] Preparation Example 9, a montmorillonite-based bifunctional catalyst, was prepared according to the following method:
[0057] 10 g of sodium montmorillonite (ion exchange capacity 0.9 mmol / g) was added to a 10% nitric acid aqueous solution, stirred and mixed for 8 hours, and then centrifuged, washed and dried to obtain acid-activated sodium montmorillonite;
[0058] 0.05 g of magnesium nitrate was added to 250 mL of ethanol, and 10 g of acid-activated sodium montmorillonite was added, and the mixture was stirred at 50° C. for 6 h. Finally, the magnesium ion-exchanged acid-activated sodium montmorillonite was obtained by filtering, washing and drying.
[0059] 10 g chitosan (weight average molecular weight 3.28 × 10 5 , deacetylation degree 85.6%) was added to 500 mL of water, the pH value of the solution was adjusted to 14, and after stirring and mixing for 24 hours, 55 g of 2-chloroethylamine hydrochloride was added, and the reaction was stirred for 12 hours. After dialysis and freeze-drying, quaternary ammonium chitosan was obtained;
[0060] Take 10g of magnesium ion exchanged acid-activated sodium-based montmorillonite and disperse it in 250mL of water to obtain a montmorillonite suspension; add 8g of the quaternized chitosan obtained above to 250mL of water, adjust the pH value to 4.5, stir until completely dissolved and then add it to the montmorillonite suspension, increase the temperature to 60°C, stir and react for 7h, and finally obtain a montmorillonite-based bifunctional catalyst through centrifugation, washing and neutralization, drying and grinding.
[0061] Preparation Example 10, a montmorillonite-based bifunctional catalyst, is different from Example 1 only in that an equal amount of hexadecyltrimethylammonium chloride is used to replace the quaternized chitosan.
[0062] Example
[0063] Example 1, a tetramethyl bisphenol F cyanate, is prepared according to the following process steps:
[0064] S1. Take 122.2 g of 2,6-dimethylphenol and add it to 500 mL of ethanol, raise the temperature to 50°C, and stir to dissolve to obtain a 2,6-dimethylphenol solution;
[0065] S2. Add 18 g of formaldehyde to ethanol to obtain a formaldehyde solution having a mass fraction of 30%;
[0066] S3. Add formaldehyde solution and 0.8 g of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 to the 2,6-dimethylphenol solution, adjust the reaction temperature to 60 ° C, stir the reaction for 3 h, and then wash, distill under reduced pressure and dry to obtain a mixture of tetramethyl bisphenol F;
[0067] S4. 353 g of the obtained tetramethyl bisphenol F mixture was added to 1000 mL of toluene, 242.9 g of triethylamine was added, and the mixture was stirred to obtain a pre-reaction solution;
[0068] S5. Take 135.3g of cyanogen chloride and add it to 500mL of toluene. After mixing evenly, add it to the pre-reaction solution, adjust the reaction temperature to -5°C, stir the reaction for 2h, and then wash, dry, filter, vacuum distill and recrystallize to obtain tetramethyl bisphenol F cyanate.
[0069] Example 2, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the amount of formaldehyde added is 16.5 g; the montmorillonite-based bifunctional catalyst prepared in Preparation Example 2 is used to replace the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1; the amount of triethylamine added is 232.8 g, and the amount of cyanogen chloride added is 123 g.
[0070] Example 3, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 is replaced by an equal amount of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 3; the amount of triethylamine added is 263.1 g, and the amount of cyanogen chloride added is 141.5 g.
[0071] Example 4, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the amount of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 added is 0.25 g.
[0072] Example 5, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the amount of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 added is 1.8 g.
[0073] Example 6, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 is replaced by an equal amount of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 4.
[0074] Example 7, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 is replaced by an equal amount of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 5.
[0075] Example 8, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the amount of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 added is 2.5 g.
[0076] Example 9, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 is replaced by an equal amount of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 9.
[0077] Comparative Example
[0078] Comparative Example 1, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 is replaced by an equal amount of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 6.
[0079] Comparative Example 2, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 is replaced by an equal amount of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 7.
[0080] Comparative Example 3, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 is replaced by an equal amount of the montmorillonite-based catalyst prepared in Preparation Example 8.
[0081] Comparative Example 4, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 is replaced by an equal amount of the montmorillonite-based bifunctional catalyst prepared in Preparation Example 10.
[0082] Comparative Example 5, a tetramethyl bisphenol F cyanate, is different from Example 1 only in that the montmorillonite-based bifunctional catalyst prepared in Preparation Example 1 is not added during the preparation process.
[0083] Performance testing
[0084] The yield of each embodiment and comparative example and the purity of tetramethyl bisphenol F cyanate were calculated and tested, and the test results are shown in Table 1:
[0085] Table 1 Test results
[0086]
[0087] According to Table 1, in combination with Example 1 and Example 2 to Example 5, it can be seen that the yield and purity of Example 2 to Example 5 are not significantly different from those of Example 1. The reason is that compared with Example 1, Example 2 to Example 5 only change the raw materials and the raw material ratio within the required range, which has little effect on the yield and purity of the final product.
[0088] In combination with Example 1, Example 6, Example 7 and Comparative Example 3, it can be seen that the yield and purity of Example 6, Example 7 and Comparative Example 3 are reduced compared to Example 1, and the reduction in Comparative Example 3 is the most obvious. The reason is that in Example 6, the content of the montmorillonite-based bifunctional catalyst intercalated composite quaternized chitosan is reduced, resulting in a reduction in the alkaline active sites contained in the catalyst, which will affect the preparation of tetramethyl bisphenol F cyanate. In Comparative Example 3, montmorillonite is not intercalated and composited, and the obtained catalyst does not have a dual catalytic property, and the catalytic effect of tetramethyl bisphenol F cyanate is significantly reduced, so the yield is significantly reduced. In Example 7, the content of the montmorillonite-based bifunctional catalyst intercalated composite quaternized chitosan is increased, which will affect the acid sites on the surface of montmorillonite on the one hand, causing a reduction in acid sites, and on the other hand, it will also cause the montmorillonite interlayer spacing to be too large, and the structural stability of the catalyst will decrease, which will affect the catalytic activity of the catalyst.
[0089] Combining Example 1 and Example 8, it can be seen that the yield and purity of Example 8 are lower than those of Example 1, especially the purity decreases significantly. The reason is that the amount of montmorillonite-based bifunctional catalyst added in Example 8 is increased. Excessive addition of the catalyst will catalyze the production of side reaction products, resulting in a decrease in the purity of tetramethyl bisphenol F, thereby affecting the yield and purity of tetramethyl bisphenol F cyanate.
[0090] Combining Example 1 and Example 9, it can be seen that the yield and purity of Example 9 are increased compared with Example 1. The reason is that in the preparation process of the montmorillonite-based bifunctional catalyst in Example 9, the acid-activated sodium-based montmorillonite is also subjected to magnesium ion exchange treatment, which on the one hand will increase the activity of the acid-base sites and the selectivity of the catalyst, thereby improving the catalytic activity; on the other hand, it will also increase the binding force between the quaternized chitosan and montmorillonite, prevent the loss of chitosan, and avoid the introduction of impurities in the preparation process of tetramethyl bisphenol F cyanate.
[0091] Combining Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 4, it can be seen that the yield and purity of Comparative Example 1, Comparative Example 2 and Comparative Example 4 are significantly reduced compared with those of Example 1. The reason is that the montmorillonite-based bifunctional catalyst in Comparative Example 1 does not perform acid activation pretreatment on montmorillonite, resulting in a decrease in the acid site content and activity of the catalyst, affecting the purity of tetramethyl bisphenol F, and further affecting the yield and purity of tetramethyl bisphenol F cyanate; the chitosan intercalated with the montmorillonite-based bifunctional catalyst in Comparative Example 2 has not undergone a quaternization reaction, which will affect the interface between chitosan and montmorillonite on the one hand, and reduce the basic sites in the montmorillonite-based bifunctional catalyst on the other hand, thereby affecting the catalytic activity of tetramethyl bisphenol F cyanate; in Comparative Example 4, no montmorillonite-based bifunctional catalyst is added, the purity of tetramethyl bisphenol F is not high, and the introduction of by-products and impurities will affect the subsequent synthesis of tetramethyl bisphenol F cyanate, affecting the final material performance, yield and purity.
[0092] In combination with Example 1, Comparative Example 4 and Comparative Example 5, it can be seen that the yield and purity of Comparative Example 5 are decreased compared with Example 1, and slightly increased compared with Comparative Example 4. The reason is that in Comparative Example 5, a general quaternary ammonium salt is used to replace the quaternized chitosan to modify the montmorillonite. Compared with chitosan, the molecular weight of the general quaternary ammonium salt is small and the active sites are few. Therefore, when the intercalation composite is performed, it is not conducive to the improvement of the montmorillonite interlayer spacing, thereby affecting the selectivity of the catalyst, reducing the catalytic activity of the montmorillonite, and the structural stability is also reduced.
[0093] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0094] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing tetramethyl bisphenol F cyanate, characterized in that: The process steps include: S1. Add 2,6-dimethylphenol to solvent A, raise the temperature to 45-55° C., and stir to dissolve to obtain a 2,6-dimethylphenol solution; S2. adding formaldehyde to solvent A to obtain a formaldehyde solution having a mass fraction of 30 to 40%; S3. Adding formaldehyde solution and montmorillonite-based bifunctional catalyst to 2,6-dimethylphenol solution, adjusting the reaction temperature to 50-70° C., stirring the reaction for 2-3 h, and then washing, vacuum distillation and drying to obtain a mixture of tetramethyl bisphenol F; S4. The obtained mixture of tetramethyl bisphenol F is added to solvent B, triethylamine is added, and the mixture is stirred to obtain a pre-reaction solution; S5. Add cyanogen chloride to solvent B, mix well and then add to the pre-reaction solution, adjust the reaction temperature to -5 to 0°C, stir the reaction for 1.5 to 2.5 hours, and then wash, dry, filter, vacuum distill and recrystallize to obtain tetramethyl bisphenol F cyanate; The montmorillonite-based bifunctional catalyst is intercalated with composite quaternized chitosan.
2. The method for preparing tetramethyl bisphenol F cyanate according to claim 1, characterized in that: The addition amount of the montmorillonite-based bifunctional catalyst is 0.2-1.5% of the mass of 2,6-dimethylphenol.
3. The method for preparing tetramethyl bisphenol F cyanate according to claim 1, characterized in that: The raw materials of the montmorillonite-based bifunctional catalyst include acid-activated sodium-based montmorillonite and quaternized chitosan in a mass ratio of 1:(0.75-0.85).
4. The method for preparing tetramethyl bisphenol F cyanate according to claim 3, characterized in that: The montmorillonite-based bifunctional catalyst is prepared according to the following method: Preparation of acid-activated sodium montmorillonite: adding sodium montmorillonite to a strong acid aqueous solution with a mass fraction of 10 to 15%, stirring and mixing for 6 to 8 hours, centrifuging, washing and drying to obtain acid-activated sodium montmorillonite; Preparation of quaternized chitosan: chitosan is added to water, the pH value of the solution is adjusted to 14-14.5, after stirring and mixing for 12-24 hours, a quaternary ammonium agent aqueous solution is added, and the reaction is stirred for 10-12 hours, and the quaternized chitosan is obtained by dialysis and freeze drying; Preparation of montmorillonite-based bifunctional catalyst: acid-activated sodium montmorillonite is dispersed in water to obtain a montmorillonite suspension; quaternized chitosan is added to water, the pH value is adjusted to 4.5-5, stirred until completely dissolved and then added to the montmorillonite suspension, the temperature is increased to 50-60°C, stirred for reaction for 6-8h, and finally centrifuged, washed, neutralized, dried and ground to obtain a montmorillonite-based bifunctional catalyst.
5. The method for preparing tetramethyl bisphenol F cyanate according to claim 4, characterized in that: The quaternizing agent includes one or more combinations of 2-chloroethylamine hydrochloride, 3-chloropropylamine hydrochloride, 2-bromoethylamine hydrochloride, 4-chlorobutylamine hydrochloride, 2-chloroethyltrimethylammonium chloride and (2-bromoethyl)trimethylammonium bromide.
6. The method for preparing tetramethyl bisphenol F cyanate according to claim 3, characterized in that: The acid-activated sodium-montmorillonite is treated with magnesium ion exchange; the magnesium ion exchange treatment comprises the following steps: adding magnesium salt to a solvent, stirring and mixing, adding acid-activated sodium-montmorillonite, stirring and mixing at 50-60° C. for 5-6 hours, and finally filtering, washing and drying to obtain the acid-activated sodium-montmorillonite exchanged with magnesium ions.
7. The method for preparing tetramethyl bisphenol F cyanate according to claim 6, characterized in that: The magnesium salt comprises a combination of one or more of magnesium chloride, magnesium sulfate, magnesium nitrate and magnesium acetate; the added amount of the magnesium salt is 0.4-0.6% of the mass of the acid-activated sodium-based montmorillonite.
8. The method for preparing tetramethyl bisphenol F cyanate according to claim 1, characterized in that: The solvent A includes one of ethanol, methanol, acetone, dimethylformamide and ethyl acetate; the solvent B includes one of butanone, toluene, dichloromethane and isopropanol.
9. The method for preparing tetramethyl bisphenol F cyanate according to claim 1, characterized in that: The molar ratio of the 2,6-dimethylphenol to formaldehyde is 1:(0.55-0.6); the molar ratio of the tetramethyl bisphenol F mixture, cyanogen chloride and triethylamine is 1:(2.3-2.6):(2-2.3).
10. A tetramethyl bisphenol F cyanate, characterized in that The tetramethyl bisphenol F cyanate is prepared according to the preparation method of tetramethyl bisphenol F cyanate according to any one of claims 1 to 9.